Seismic Structure Study of Buzurgan Oil field, Southern Iraq - Aldarraji, Mustafa Qasim; Almayahi, Ali Zbarie (Iraqi Journal of Science, 2019)
The Buzurgan oil field is one of the most important oil fields border in southern Iraq.Adjacent to the Fauqi and Abu Ghirab oil fields common with Iran. The 3D seismic data showed the structural and stratigraphic of the Buzurgan oil field, where the results showed that the structure is an anticline fold with two structural domes separated by a saddle, the northern culmination is shallower and less deformation. Thirty-one faults were detected and most of them at the south part of the field which are small while the north faults are larger.